Pengaruh Kualitas Pelayanan, Harga, dan Fasilitas terhadap Kepuasan Penumpang pada PT. ASDP Indonesia Ferry (Persero) Cabang Kupang - Poma, Sarlianus (Business Management Journal, 2024)
East Nusa Tenggara is one of the provinces in Indonesia which is known as an archipelagic province. As an archipelagic province, PT. ASDP Indonesia Ferry (Persero) Kupang Branch is considered an important service to be able to connect one area with another area. Service quality, price, and facilities are important factors related to passenger satisfaction. Passenger satisfaction in using sea transportation services is of course determined by several factors taken by researcher in this research, namely service quality, price, and facilities offered by PT. ASDP Indonesia Ferry (Persero) Kupang Branch. The research aims to determine the influence of service quality, price, and facilities on passenger satisfaction, both simultaneously and partially. The research population is PT service users ASDP Indonesia Ferry (Persero) Kupang Branch with a total of 55 respondents. Purposive sampling was chosen by the researcher as the sampling technique. Multiple linear regression analysis was carried out to analyze the data with the help of SPSS 25.0 for Windows. The results show that service quality, price, and facilities simultaneously affect passenger satisfaction, service quality partially has no effect on passenger satisfaction, price partially has no effect on passenger satisfaction and facilities partially influence passenger satisfaction.